1975
DOI: 10.1007/bf00147165
|View full text |Cite
|
Sign up to set email alerts
|

Rapid method of determining pollen incompatibility in Chrysanthemum morifolium Ramat

Abstract: A classification system for predicting high, medium and low seed set from Chrysanthemum morifolium crosses was developed. Stigmas collected and preserved 8 days after pollination were examined with a binocular microscope for adhering pollen grains. Florets from compatible crosses had brown stigmas with pollen grains attached and embryo development while florets from incompatible crosses had white stigmas with no or rarely 1 or 2 pollen grains attached and no embryo development. Using this method the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The hypothesis tested was that the seed development time between laboratory and in situ conditions would not differ. 'Bluechip', a greenhouse cultivar (Table 1), was chosen for use in this study, since the rate of embryogenesis up to the heart stage has been previously reported (Drewlow et al, 1975;Watanabe, 1977). Outcross pollinations were performed using a composite male bulk pollen source to minimize matched S alleles that would cause cross incompatibility.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis tested was that the seed development time between laboratory and in situ conditions would not differ. 'Bluechip', a greenhouse cultivar (Table 1), was chosen for use in this study, since the rate of embryogenesis up to the heart stage has been previously reported (Drewlow et al, 1975;Watanabe, 1977). Outcross pollinations were performed using a composite male bulk pollen source to minimize matched S alleles that would cause cross incompatibility.…”
Section: Methodsmentioning
confidence: 99%
“…Whole plots were the sampling dates of 8, 9, 11, 19, and 24 days postpollination, at which time the in florescences were removed from the plants. Day 8 was selected as the first sampling date because earlier dates were at the pre-heart stage (Drewlow et al, 1975) and could not be ER without using Norstog medium. Each seed head was divided in half (as split-plots) following disinfestation in 95% ethanol (for 1 rein) under a Iaminar flow hood; the embryos were rescued either with or without seed coat removal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However it was possible to use the pollens after long storage period over 2 months at low temperature (-75 0 C and -20 0 C). When a cross is incompatible in chrysanthemum, no pollen grain attaches to the stigma as reported by Drewlow et al, (1975) and Myung et al, (2006a). Inhibition of pollen tube growth occurred in stigmatic surface and reciprocal differences in crosses were also found (Drewlow et al, 1973).…”
Section: Hybridizationmentioning
confidence: 56%
“…Recent studies revealed that chrysanthemum is a segmental allohexaploid with an ambiguous pattern of inheritance (Klie et al, 2014). Moreover, self-incompatibility (SI) resulting from the existence of a sporophytic system complicates inheritance studies, as well as homozygous plant production, which is crucial in the breeding process (Drewlow et al, 1973;Wang et al, 2014b). The application of haploids and doubled haploids can solve many problems related to cross breeding, as well as genetic studies on chrysanthemum.…”
Section: Introductionmentioning
confidence: 99%